Lumut Sutra (Chaetomorpha sp.) Sebagai Pakan Alternatif Untuk Pertumbuhan dan Kelangsungan Hidup Ikan Nila (Oreochromis niloticus) Di Distrik Ayamaru Utara Kabupaten Maybrat - Jeklentina Homer; Ratna Ratna; Ahmad Fahrizal (INTEGRATED OF FISHERIES SCIENCE, 2025)
Yubiah Village is a village located in North Ayamaru District, Maybrat Regency, West Papua Province. The community of Yubiah Village is largely engaged in freshwater fish farming, and one of the main cultured species is Nile tilapia. This fish is chosen not only because it is easy to cultivate but also because it has good marketability. Freshwater sources in Yubiah Village are abundant, making freshwater aquaculture easy to carry out. The purpose of this study was to determine the effect of silk algae (Chaetomorpha sp.) as an alternative feed on the growth and survival of Nile tilapia. The research was conducted from October to November 2022 in Yubiah Village, North Ayamaru District, Maybrat Regency, West Papua Province. This study used a Completely Randomized Design (CRD) consisting of three treatments and one control. The results of the study led to the following conclusions: The measurement of absolute weight gain of Nile tilapia showed that the best growth occurred in Treatment C with 80 grams of silk algae as an alternative feed, followed by Treatment B with 60 grams, and Treatment A with 75 grams, while the lowest growth was obtained in Treatment D (without silk algae). The highest survival rate of Nile tilapia was found in Treatment C (28 grams), where fish were given a higher amount of silk algae three times a week. This was followed by the other treatments.